2012
DOI: 10.1021/ja307956w
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Functionalization of Methyl Group on Silicon: Iridium-Catalyzed C(sp3)–H Borylation of Methylchlorosilanes

Abstract: A methyl group of methylchlorosilanes undergoes C-H borylation in an iridium-catalyzed reaction with bis(pinacolato)diboron in cyclohexane at 80 °C, giving (borylmethyl)chlorosilanes selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 52 publications
1
56
0
4
Order By: Relevance
“…Another important reason is that diborane is very reactive and thereby the oxidative addition of diborane easily occurs to the iridium(I) boryl species to afford the iridium(III) triboryl complex, indicating that the iridium(I) boryl complex cannot exist as a stable species under the catalytic reaction conditions. Actually, This type of CH σ-bond activation followed by borylation with diborane is an attractive catalytic reaction and many reports have been presented to date 108,109,115,116 because the C H bond activation and the functionalization are achieved at one time. One important development of this reaction is the extension to the borylation of a C(sp 3 )H bond.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 99%
See 1 more Smart Citation
“…Another important reason is that diborane is very reactive and thereby the oxidative addition of diborane easily occurs to the iridium(I) boryl species to afford the iridium(III) triboryl complex, indicating that the iridium(I) boryl complex cannot exist as a stable species under the catalytic reaction conditions. Actually, This type of CH σ-bond activation followed by borylation with diborane is an attractive catalytic reaction and many reports have been presented to date 108,109,115,116 because the C H bond activation and the functionalization are achieved at one time. One important development of this reaction is the extension to the borylation of a C(sp 3 )H bond.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 99%
“…This reaction was shown to be facile in the recently reported Ir-catalyzed C(sp 3 ) H borylation of chlorosilane. 116 A recent DFT study reported that the reaction occurs via oxidative addition of the C(sp 3 )H bond to the iridium(III) triboryl complex followed by the reductive elimination of borylated product, 117 which is essentially the same as the mechanism of Ir-catalyzed borylation of benzene. Also, the C(sp Another important development is to achieve regioselective CH σ-bond activation in these direct borylation reactions, which is also an important target in the chemistry of CH activation because regioselective CH σ-bond activation is not easy.…”
Section: Catalyses For Hydrosilylation Of Alkenementioning
confidence: 99%
“…Complete conversion of 4 into iPr 3 SiH and benzene by B(C 6 F 5 ) 3 was however observed. As the trimethylsilyl group is not easily functionalized, [14] we included precursor 5 with a phenyl-substituted silicon atom into our survey. That would later allow for oxidative degradation of the C À Si bond.…”
mentioning
confidence: 99%
“…Die vollständige Überführung von 4 in iPr 3 SiH und Benzol durch B(C 6 F 5 ) 3 wurde dennoch beobachtet. Da die Funktionalisierung der Trimethylsilylgruppe schwierig ist, [14] bezogen wir die Vorstufe 5 mit einem phenylsubstituierten Siliciumatom mit in unsere Untersuchung ein. Das bçte später die Mçglichkeit zum oxidativen Abbau der C-Si-Bindung.…”
Section: Methodsunclassified